RAGAM BAHASA GAUL DALAM FILM BUCIN KARYA CHANDRA LIOW - Ma'ruf, Zilzia Rahmi; Sulissusiawan, Ahadi; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Slang language research aims to classify and analyze the form, meaning, types of changes in meaning and function of slang words in the film Bucin by Chandra Liow using sociolinguistic studies. The method used in the research is descriptive method with qualitative research form. The data source in this research is the movie Bucin by Chandra Liow. The data in this study are slang words contained in the movie Bucin by Chandra Liow. The data colletion technique used in this research is documentation study. Based on the results of data analysis in this study, it can be conlcluded that the data obtained amounted to 95 data. The category of slang word form consists of phoneme reduction as much as 12 data. The slang word form in the form of phoneme addition is 10 data. Slang word form in the form of shortening as much as 23 data. Word borrowing consisting of local and foreign languages amounted to 11 data, monophthongization amounted to 3 data, Letter replacement amounted to 12 data, puns amounted to 1 data, reduplication amounted to 1 data, affixation amounted to 6 data, the formation of new vocabulary amounted to 8 data, the use of particles amounted to 7 data and word reversal amounted to 1 data